2000
DOI: 10.1034/j.1399-302x.2000.150405.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virulence factors of oral Candida dubliniensis and Candida albicans isolates in healthy people and patients with chronic candidosis

Abstract: We determined differences in the expression of certain virulence factors between oral Candida dubliniensis and Candida albicans species. In addition, clonal differences were sought among C. albicans isolates recovered from patients with and without compromised immune system. The material comprised 93 clinical yeast isolates originated in 40 subjects (1-5 isolates per subject). All 26 C. dubliniensis isolates and 46 C. albicans isolates originated from healthy routine dental clinic patients. Additionally, 21 C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1
11

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 39 publications
7
41
1
11
Order By: Relevance
“…Some patients show stains with reduced genetic diversity (7,43), even though other patients can show alterations in the frequency of phenotypes and genotypes of C. albicans (3,43,44), suggesting the existence of a dynamic process of colonization of these species, or the difficulty still in establishing a more defined comparison the phenotypic and genotypic diversity of these microorganisms, using the available methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients show stains with reduced genetic diversity (7,43), even though other patients can show alterations in the frequency of phenotypes and genotypes of C. albicans (3,43,44), suggesting the existence of a dynamic process of colonization of these species, or the difficulty still in establishing a more defined comparison the phenotypic and genotypic diversity of these microorganisms, using the available methods.…”
Section: Discussionmentioning
confidence: 99%
“…These results are also partly in agreement with results reported by (1), which demonstrated that 83.3% and 71.9% of the C. albicans strains produced this enzyme, when isolated from niches with and without lesions characteristic of candidiasis, respectively. However, in comparing virulence factors of C. albicans and C. dubliniensis, isolated from healthy individuals and patients with chronic candidiasis, showed that 52% of the C. albicans strains isolated from immuno-compromised patients and 60% from healthy patients produced phospholipase (7).…”
Section: Discussionmentioning
confidence: 99%
“…Many techniques are available to detect Candida species in clinical samples, including fungal culture, PAS staining, Grocott's methenamine silver staining, immunostaining, PCR, and LAMP (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic C. albicans infections of the oral cavity are a known risk factor for aspiration pneumonia (11). Several detection methods for C. albicans are available, including microbial culture, microscopic examination (PAS staining, Grocott's methenamine silver staining) and biochemical techniques (indirect hemagglutination, counterimmunoelectrophoresis), polymerase chain reaction (PCR), and real-time PCR (12)(13)(14)(15)(16)(17). However, these methods require technical expertise and complex devices, and diagnosis using them is time-consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…Candida dubliniensis, espécie recentemente descrita por SULLIVAN et al (1995), e isolada principalmente da mucosa bucal de indivíduos infectados pelo HIV SULLIVAN et al, 1995), tem sido encontrada também em pacientes clinicamente saudáveis (HANNULA et al, 2000;PINJON et al, 1998 INSTITUTE, 1998;GUIDELINES, 2000).…”
Section: Lista De Figurasunclassified